Nurses ethical dilemmas in responding to requests to withdraw life-sustaining treatment: A qualitative study from bioethical and Maqashid Al-Shariah perspectives - Lulu Azizah Zahro; Alyya Dwiyulianti Pratiwi; Lugita Julian Pamungkas; Nabila Komarudin; R Intania Putri Az Zahra; Tedi Supriyadi; Akhmad Faozi (School of Health Sciences Al-Ma'arif, 2026)
Background: Ethical dilemmas surrounding the limitation of life-sustaining treatment in patients experiencing medical futility remain complex because they involve clinical, ethical, legal, and religious considerations. Nurses frequently encounter these situations because of their close involvement with patients and families during end-of-life care. Purpose: This study aimed to explore nurses’ ethical dilemmas in responding to the limitation of life-sustaining treatment from bioethical and maqashid al-Shari’ah perspectives. Methods: This descriptive qualitative study used purposive sampling. Eleven participants, comprising seven nursing professionals and four religious leaders from Sumedang and Bandung, Indonesia, were recruited. Data were collected through in-depth, semi-structured interviews and analyzed using the Miles and Huberman interactive analysis model. Results: Four major themes emerged: (1) limitations of nurses’ authority in decision-making; (2) nurses’ roles as patient advocates and communication mediators; (3) integration of bioethical principles and maqashid al-Shari’ah in treatment limitation under conditions of medical futility; and (4) transformation of nursing care toward palliative and spiritual approaches. Participants emphasized that nurses do not have independent authority to discontinue life-sustaining treatment but play essential roles in advocacy, communication, comfort care, and spiritual support. Treatment-limitation decisions were understood as multidisciplinary clinical decisions guided by bioethical principles and the concept of hifz al-nafs. Conclusions: Ethical dilemmas related to treatment limitation in medical futility require an integrative approach combining clinical, ethical, legal, and spiritual considerations. The findings highlight the importance of collaboration among healthcare professionals, families, and religious leaders in supporting ethical, patient-centered end-of-life care.